The Four Main Principles That Become the Pillars of Legal Building National Treaty - Muhammad Arifin (Universitas Muhammadiyah Sumatera Utara, 2022)
Contract law as regulated in Book III of the Criminal Code. Civil Code is a legacy of the Dutch Colonial which is more than a century and a half old. Considering the development of the business world which is closely related to the law of agreement or contract, it becomes a sine qua non to reform the law of agreement. The renewal of treaty law cannot be separated from the search for legal principles that serve as the basic foundation so that legal issues arise to seek and find the legal principles that are the pillars of the building of national treaty law. This research is a normative juridical research, namely research that conducts an assessment of library materials. The data source used is secondary data. Secondary data is data sourced from library research related to publications, namely library data listed in official documents. The search and discovery of these legal principles is carried out through normative legal studies by relying on the search for various theoretical legal materials obtained from literature studies. The results of the study found four main legal principles as the main pillars of the building of national contract law, namely the principle of consensualism, the principle of freedom of contract, the principle of binding contractual power and the principle of good faith